1996
DOI: 10.1523/jneurosci.16-04-01422.1996
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide Y1 receptors inhibit N-type calcium currents and reduce transient calcium increases in rat dentate granule cells

Abstract: Neuropeptide Y (NPY) is far more abundant in the dentate gyrus than elsewhere in the hippocampal formation, but it does not alter the synaptic excitation of dentate granule cells (DGCs) as it does for pyramidal cells in areas CA1 and CA3. NPY inhibited depolarization-induced increases in intracellular Ca2+ concentrations ([Ca2+]i) in DGCs in hippocampal slices, without altering the resting [Ca2+]i. NPY inhibited Ca2+ currents (ICa) via a Y1 receptor in 84% of acutely isolated DGCs and via a Y2 receptor in 31% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 50 publications
(17 reference statements)
4
49
1
Order By: Relevance
“…Autoradiographic binding studies and in situ hybridization have shown that Y1 and Y2 receptors are quite abundant in the rat hippocampus (Dumont et al, 1990(Dumont et al, , 1992McQuiston et al, 1996;Wahlestedt and Reis, 1993;McQuiston et al, 1996). According to some earlier results obtained by our group and by other authors (Sajdyk et al, 1999;Wierońska et al, 2004Wierońska et al, , 2005, NPY shows anxiolytic activity in the amygdala, and this effect is mediated by Y1 receptors, as it is blocked by BIBO 3304.…”
Section: Anxiolytic Effect Of Intrahippocampal Mglur Ligands and Npy mentioning
confidence: 73%
“…Autoradiographic binding studies and in situ hybridization have shown that Y1 and Y2 receptors are quite abundant in the rat hippocampus (Dumont et al, 1990(Dumont et al, , 1992McQuiston et al, 1996;Wahlestedt and Reis, 1993;McQuiston et al, 1996). According to some earlier results obtained by our group and by other authors (Sajdyk et al, 1999;Wierońska et al, 2004Wierońska et al, , 2005, NPY shows anxiolytic activity in the amygdala, and this effect is mediated by Y1 receptors, as it is blocked by BIBO 3304.…”
Section: Anxiolytic Effect Of Intrahippocampal Mglur Ligands and Npy mentioning
confidence: 73%
“…This is also suggested by electrophysiological studies, which have shown that NPY influences mossy fiber transmission by a presynaptic mechanism [10]. Both Y2 and Y5 receptors have been implicated in these effects [15,16].…”
Section: Normal Localization Of Npy and Its Receptors In The Rat Dentmentioning
confidence: 70%
“…Studies of Y1 receptor agonists reveal inhibitory effects on Ca 2+ entry into dendrites of granule cells [16]. Other studies suggest a potentially proconvulsant effect [17].…”
Section: Normal Localization Of Npy and Its Receptors In The Rat Dentmentioning
confidence: 99%
“…Sleep loss upregulates CNS food-reward systems BA Baldo et al localized in interneurons (Hendry et al, 1984;Karagiannis et al, 2009), and hippocampal NPY is found both in GABA interneurons (Sperk et al, 2007) and granule cells (McQuiston et al, 1996). The role of NPY in hippocampus is not fully understood; however, several studies suggest a role in cellular defenses against excitatory stress.…”
Section: Sleep Deprivation Npy Expression and Hippocampal Plasticitymentioning
confidence: 99%
“…For example, NPY gene expression is upregulated by metabotropic glutamate receptor stimulation (Schwartzer and Sperk, 1998) and NPY in the dentate gyrus inhibits glutamate release (Whittaker et al, 1999) has anticonvulsive actions (Patrylo et al, 1999). NPY also reduces depolarization-induced Ca 2 þ influx into dentate granule cells (McQuiston et al, 1996), which could be responsible for NPY-induced inhibition of perforant pathway LTP (Whittaker et al, 1999). Hippocampal NPY may thus serve a neuroprotective role during conditions of cellular stress, but at the same time inhibit neuroplasticity relevant to learning.…”
Section: Sleep Deprivation Npy Expression and Hippocampal Plasticitymentioning
confidence: 99%